2019
DOI: 10.3389/fimmu.2019.00669
|View full text |Cite
|
Sign up to set email alerts
|

Complement in Metastasis: A Comp in the Camp

Abstract: The complement system represents a pillar of the innate immune response. This system, critical for host defense against pathogens, encompasses more than 50 soluble, and membrane-bound proteins. Emerging evidence underscores its clinical relevance in tumor progression and its role in metastasis, one of the hallmarks of cancer. The multistep process of metastasis entails the acquisition of advantageous functions required for the formation of secondary tumors. Thus, targeting components of the complement system c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(19 citation statements)
references
References 109 publications
0
19
0
Order By: Relevance
“…Cancer cells-derived C3a also adapts the cerebrospinal fluid for leptomeningeal metastasis by activation of C3aR on the choroid plexus epithelium, disrupting thus the blood-cerebrospinal fluid barrier 57 . The role of complement for cancer metastases is reviewed elsewhere 58 .…”
Section: Direct Impact Of Complement Effectors On Tumor Cell Biologymentioning
confidence: 99%
“…Cancer cells-derived C3a also adapts the cerebrospinal fluid for leptomeningeal metastasis by activation of C3aR on the choroid plexus epithelium, disrupting thus the blood-cerebrospinal fluid barrier 57 . The role of complement for cancer metastases is reviewed elsewhere 58 .…”
Section: Direct Impact Of Complement Effectors On Tumor Cell Biologymentioning
confidence: 99%
“…Despite this, in recent years advances have been made in understanding the relationship between complement and cancer with several studies demonstrating pro-tumorigenic roles for complement. Several excellent reviews have recently discussed the role of complement in tumour growth and dissemination in detail [3,19,113].…”
Section: Complement In Tumour Growthmentioning
confidence: 99%
“…Furthermore, complement has also been reported to induce angiogenesis [15,119,123] and foster acquisition of an epithelial-mesenchymal transition (EMT) phenotype by promoting expression of stemness genes [122], enhancing invasion [124][125][126] and increasing motility [127][128][129][130] of cells in several cancer types. Detailed overviews of the roles played by complement components in facilitating metastasis have recently been published by Ajona et al [113] and Kochanek et al [131].…”
Section: Murine Studiesmentioning
confidence: 99%
“…We also observed a change in the expression of ECM-associated factors in Rreb1 -/embryos, some of which have been linked to changes in the metastatic potential of cells. Furthermore, KEGG pathway analysis of downregulated genes revealed that these were associated with the complement and coagulation cascades, which control a variety of processes, including ECM remodeling, and the corruption of this pathway is linked to cancer metastasis (Ajona, Ortiz-Espinosa, Pio, & Lecanda, 2019). Thus, changes in ECM composition in Rreb1 -/embryos may drive invasive behaviors.…”
Section: Discussionmentioning
confidence: 99%